Life cycle assessment shows admixtures support high-performance low-carbon LC3 concrete - Pippa Edwards; Sébastien Dhers; Rupert J. Myers (Resources, Conservation and Recycling, 2026)

Temporal and spatial drivers of the structure of macroinvertebrate assemblages associated with Laminaria hyperborea detritus in the northeast Atlantic - Adam Gouraguine; Dan A. Smale; Arwyn Edwards; Nathan G. King; Mathilde Jackson-Bué; Sean Kelly; Hannah S. Earp; Pippa J. Moore (Marine Environmental Research, 2024)

Peatland pools are tightly coupled to the contemporary carbon cycle - Joshua F. Dean; Michael F. Billett; T. Edward Turner; Mark H. Garnett; Roxane Andersen; Rebecca M. McKenzie; Kerry J. Dinsmore; Andy J. Baird; Pippa J. Chapman; Joseph Holden (Global Change Biology, 2024)
Peatlands are globally important stores of soil carbon (C) formed over millennial timescales but are at risk of destabilization by human and climate disturbance. Pools are ubiquitous features of many peatlands and can contain very high concentrations of C mobilized in dissolved and particulate organic form and as the greenhouses gases carbon dioxide (CO 2 ) and methane (CH 4 ). The radiocarbon content ( 14 C) of these aquatic C forms tells us whether pool C is generated by contemporary primary production or from destabilized C released from deep peat layers where it was previously stored for millennia. We present novel 14 C and stable C (δ 13 C) isotope data from 97 aquatic samples across six peatland pool locations in the United Kingdom with a focus on dissolved and particulate organic C and dissolved CO 2 . Our observations cover two distinct pool types: natural peatland pools and those formed by ditch blocking efforts to rewet peatlands (restoration pools). The pools were dominated by contemporary C, with the majority of C (~50%–75%) in all forms being younger than 300 years old. Both pool types readily transform and decompose organic C in the water column and emit CO 2 to the atmosphere, though mixing with the atmosphere and subsequent CO 2 emissions was more evident in natural pools. Our results show little evidence of destabilization of deep, old C in natural or restoration pools, despite the presence of substantial millennial‐aged C in the surrounding peat. One possible exception is CH 4 ebullition (bubbling), with our observations showing that millennial‐aged C can be emitted from peatland pools via this pathway. Our results suggest that restoration pools formed by ditch blocking are effective at preventing the release of deep, old C from rewetted peatlands via aquatic export.